Recombinant human serum albumin for corneal preservation. Issue 1 (21st June 2017) - Parekh, Mohit; Elbadawy, Hossein; Salvalaio, Gianni; Amoureux, Marie‐Claude; Di Iorio, Enzo; Fortier, Denis; Ponzin, Diego; Ferrari, Stefano; Ruzza, Alessandro
Abstract: Purpose: To study the performance of a completely synthetic organ culture (OC) preservation system containing recombinant human serum albumin (rHSA) for preservation of human donor corneas. Methods: Twenty‐four paired donor corneas were randomly collected, and one cornea from each donor was preserved in synthetic (experimental) and serum‐based media (control). The tissues were assessed at day 0; after 6 days of preservation at room temperature (RT) in Cornea Trans ® and Cornea Prep II ® ; after 28 days at 31°C in Cornea Syn ® [with rHSA] and Cornea Max ® [with foetal calf serum (FCS)] and; 4‐day post deswelling in Cornea Trans ® and Cornea Jet ® . Thickness was determined with optical coherence tomography (OCT) and transparency with a validated, custom device. Morphology, endothelial cell density (ECD) and mortality were observed after treating the tissues with Trypan blue and sucrose. Glucose uptake by the cells was analysed. Data were compared using non‐parametric paired Wilcoxon tests with p < 0.05 deemed significant. Histology using periodic acid‐schiff (PAS), expressions of p63, CK12, α SMA and ZO‐1 were analysed, and cell apoptosis postpreservation was studied. Results: Corneas stored in synthetic media showed a higher and statistically significant value as compared to serum‐based media in terms of viable endothelial cell density (VECD), mortality, morphology and glucose uptake postpreservation. Histology showed presence of all the layers, all the markers were expressed, and no apoptosis was observed in either media. Conclusion: The new synthetic preservation system containing rHSA (and other confidential constituents) showed better preservation effects than traditional media containing serum.